Mycoparasitic interaction between Trichoderma afroharzianum strain Th2RI99 and Rhizoctonia solani = Interacción micoparasítica entre Trichoderma afroharzianum cepa Th2RI99 y Rhizoctonia solani - Melignani, Eliana (2023)
The behavior of Trichoderma afroharzianum strain Th2RI99 confronted to Rhizoctonia solani AG4-HG II in dual culture was observed under light (LM) and scanning electron microscope (SEM). There is evidence of mycoparasitism in the Trichoderma harzianum complex, but no report is available regarding T. afroharzianum, since it has been just recently described as a new species, previously identified with phylogenetic analysis with 3 genes.